MERANCANG MANAJEMEN SUMBER DAYA INSANI IBU RUMAH TANGGA, REMAJA DAN ANAK-ANAK DI DESA CINANGKA, KECAMATAN CIAMPEA, BOGOR - Tubagus Rifqy Thantawi; Bayu Purnama Putra; Ega Oviani (SAHID DEVELOPMENT JOURNAL, 2023)
This community service aims to design human resource management for housewives, youth, and children in Cinangka Village Pamijahan Subdistrict bogor District, West Java Province. In this community service, activities are carried out based on the accountability methods where this researcher refers to accountabiliy and the privision of trust. The results of this community service are researchers carry out product activities from plastic waste, namely wallets and bags. With this community service, it can be concluded that Human Resource Management( MSDI ) is a management field that includes planning, organizing, implementing, and supervising. This human resource management has sharia principles, namely : trustworthuness, believes in urgency and calls for virtue, positive thingking, disciplined, responsible, and respect others. With this principle, researchers and local residents held socialization and training in the design of making products from plastic waste that would be used as wallets and bags and the people who participated in these activities were given responsibility and mandate in reporting.